Knowledge on Foot Ulcer among Diabetic Patients: A Cross-Sectional Study in a Public Hospital (East West Medical College Journal, 2024)
Background: The main purpose of the study was the knowledge of foot ulcer among diabetic patients, a cross-sectional study in a public hospital. The number of patients who suffering from Diabetes mellitus is rapidly increasing in our country. Methods: The study was an analytical cross-sectional study. The study population consisted of males and females who were suffering from diabetes mellitus in the emergency department of Fatima General Hospital. This study was conducted in the Emergency department of Fatima General Hospital. The sample size was 119,8 weeks from October 2017 to November 2017. Data was collected through a semi-structured questionnaire. the interview was focused on obtaining information about the higher-risk foot ulcers in Diabetic patients in Dhaka. Results: The depth of knowledge of foot ulcers among the diabetic patient was poor. Employed patients were more knowledgeable than the unemployed. Also, smokers & female patients were more knowledgeable than the rest.EWMCJ Vol. 12, No. 1&2, January-July 2024: 34-42